PENGARUH PERAN AUDITOR INTERNAL DAN MORAL AUDITOR INTERNAL TERHADAP GOOD CORPORATE GOVERNANCE DENGAN KUALITAS AUDITOR SEBAGAI VARIABEL MODERATING - Hasudungan Hutasoit; Redaktur Wau; Rinda Purwani (Universitas 17 Agustus 1945 Jakarta, 2017)
This study aims to determine the effect of Moral Role of Auditor and Auditor of the Good Corporate Governance with Quality Auditor as moderating variables. The population used in this study were employees who were at the Center Commercial Complex Grand Ancol, North Jakarta. With samples obtained amounted to 280 people. Sampling was determined using purposive sampling method that is part of nonprobability sampling, which is a sampling technique with a certain considerations. The type of data used is primary data. The primary data obtained by distributing questionnaires directly to the respondent. The results of this study indicate 5 Hypothesis consisting of 2 hypothesis is accepted and 3 hypothesis is rejected, ie that the influence Role internal auditor is not significant negative effect on Good Corporate Governance, Moral Internal Auditor significant and positive impact on Good Corporate Governance, Quality Auditor significant and positive impact on Good Corporate Governance, Roles Auditor does not significantly and adversely Quality Auditor and Auditor Moral does not significantly and adversely Quality Auditor.